KEWENANGAN TEMBAK DI TEMPAT TERHADAP PELAKU KEJAHATAN OLEH APARAT KEPOLISIAN - Christin Mahdalena (2022)
Often the perpetrators of criminal acts interpret the principle of presumption of innocence excessively which makes the principle of presumption of innocence as a justification for fighting against police officers and perpetrators threatening the safety of members of the Indonesian police, so that shooting criminals on the spot by the police is a priority. This study aims to analyze and explain the regulation of shooting authority at the place of the perpetrator of a crime that can be carried out by the Police and to analyze and explain the implementation of shooting at the place carried out by the Police related to the principle of presumption of innocence. This type of research is normative legal research using case studies with a statutory, case, and conceptual approaches. The results of the study show that there is a legal basis for the implementation of shooting on the spot by the police, which is regulated in Law Number 2 of 2002 concerning the Indonesian National Police, especially Article 16 paragraph (1) letter i and Article 16 paragraph (2), Regulation of the National Police Chief Number 8 of 2009 concerning Implementation of Human Rights Principles and Standards in Carrying Out the Duties of the Indonesian National Police, especially Article 45 and the Regulation of the National Police Chief Number 1 of 2009 concerning the Use of Force in Police Actions, especially Article 13 paragraph (2). Implementation of shooting on the spot carried out by the police is linked to the principle the presumption of innocence is the function of the investigator in carrying out investigation tasks. So, the author's suggestion is that there is an improvement in the specifications of violent acts committed and shooting on the spot very much in contact with the principle of presumption of innocence, so that in its implementation it must be carried out carefully and selectively. Keywords: Authority, Shoot on the Spot, Criminals, Police Officers